Topic Modeling on Peer Interaction in Online and Mobile Learning of Higher Education: 1993-2022 - Adam Kao-Wen Weng; Hsiao-Yun Chang; Kuei-Kuei Lai; Yih-Bey Lin (MDPI AG, 2024)
The advent of the digital era has catalyzed transformative shifts in educational paradigms, seamlessly integrating sustainable education with innovative pedagogical approaches that cater to a broader spectrum of learners and educators. As the academic landscape evolves into an information-dense environment, traditional models of one-on-one feedback often fall short, resulting in delays and a lack of diverse intellectual engagement. This shift underscores the growing importance of peer feedback and asynchronous post-lesson feedback mechanisms, which have emerged as vital, process-oriented educational activities. Such mechanisms not only address the immediacy and diversity of feedback but also foster a sustainable, collaborative, and engaging learning environment that bolsters student autonomy and interaction. This study conducts a mapping review and synthesis of the literature on peer interaction, assessment, and participatory innovations in online and mobile learning within higher education, covering the period from 1993 to 2022. By employing topic modeling techniques to analyze a corpus of 485 articles, the literature was initially segmented into 19 distinct issues. These were subsequently consolidated into three major thematic models, thereby highlighting significant themes, research focal points, and prospective trends. This analytical process not only enriches the understanding of peer dynamics in digital learning settings but also integrates sustainable educational practices by promoting resource efficiency and inclusivity. The findings serve as a robust reference for future researchers aiming to explore the intersections of technology, peer interaction, and sustainability in educational settings.